2018
DOI: 10.3390/w10060677
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multiple Satellite Precipitation Products and Their Use in Hydrological Modelling over the Luanhe River Basin, China

Abstract: Satellite precipitation products are unique sources of precipitation measurement that overcome spatial and temporal limitations, but their precision differs in specific catchments and climate zones. The purpose of this study is to evaluate the precipitation data derived from the Tropical Rainfall Measuring Mission (TRMM) 3B42RT, TRMM 3B42, and Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks (PERSIANN) products over the Luanhe River basin, North China, from 2001 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 45 publications
0
34
1
Order By: Relevance
“…Precipitation is one of the most important water balance components of the global water cycle, and has great variability across different spatial and temporal scales [1,2]. The accurate observation or estimation of precipitation has important theoretical and practical significance for flood warnings, drought monitoring, and water resource management [3,4]. Gauge observations provide relatively accurate point-based measurements of precipitation [5]; however, owing to significant precipitation heterogeneity across a variety of spatiotemporal scales, rain gauge observations only represent local conditions, and can result in potential errors when interpolated to larger scales, especially in mountainous areas with complex terrain [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Precipitation is one of the most important water balance components of the global water cycle, and has great variability across different spatial and temporal scales [1,2]. The accurate observation or estimation of precipitation has important theoretical and practical significance for flood warnings, drought monitoring, and water resource management [3,4]. Gauge observations provide relatively accurate point-based measurements of precipitation [5]; however, owing to significant precipitation heterogeneity across a variety of spatiotemporal scales, rain gauge observations only represent local conditions, and can result in potential errors when interpolated to larger scales, especially in mountainous areas with complex terrain [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the error characteristics change depending on the climate region, season, altitude, and other factors [10,26]. In general, quantitative statistical and hydrological modelling evaluations are effective tools that are used to evaluate the precision of SPPs [4,17]. The former focuses on the comparison and evaluation of SPPs against gauge data or ground-based radar estimates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed a satisfactory performance, given that TRMM and CMADS rainfall data simulated the Han River streamflow with acceptable accuracy. A similar study over the Luanhe River Basin in China by Ren et al [57] concluded that TMPA-3B42 rainfall had the highest performance for estimating monthly runoff, while PERSIANN showed unsatisfactory results. Thus, the study provided information on the performance of different satellite rainfall products in hydrologic modeling for the Han River Basin.…”
Section: Calibration and Evaluation Of Trmm Satellite Precipitation Pmentioning
confidence: 85%
“…The postprocessed estimates are unavailable in NRT, due to the lack of ground-based rainfall observations, which is an essential requirement to improve the NRT SREs during postprocessing stage [19]. At the same time, the direct use of NRT SREs for disaster monitoring is problematic, as they are associated with large errors especially at local and catchment scales [28][29][30]. Hence, it is essential to employ error reduction methods to improve the NRT SREs before their application [31].…”
Section: Introductionmentioning
confidence: 99%